Application of health innovations with artificial intelligence in nursing - Boujarean, Hathaichnok; Chankham , Wariya (Thai Journal of Nursing, 2020)
Artificial intelligence innovation is widely used in the health field as it can be understood quickly and is constantly evolving. Artificial intelligence capabilities are increasingly adapted to healthcare. It is therefore imperative that nurses must have knowledge and be able to use artificial intelligence properly. This article present the concepts, principles, and evidence-based nursing practice in health innovation with artificial intelligence, artificial intelligence innovations and nursing service, the development of artificial intelligence innovations, and the implementation guideline of health innovations with artificial intelligence in nursing for organizational leaders and operating workers including the development of the way of thinking and procedures for artificial intelligence utilization in nursing incorporated with technology and health service system.